Population dynamics of PIWI-interacting RNAs (piRNAs) and their targets in Drosophila. - Lu, J.; Clark, A.G. (Genome Research, 2010)
Transposable elements (TEs) are mobile DNA sequences that make up a large fraction of eukaryotic genomes. Recently it was discovered that PIWI-interacting RNAs (piRNAs), a class of small RNA molecules that are mainly generated from transposable elements, are crucial repressors of active TEs in the germline of fruit flies. By quantifying expression levels of 32 TE families in piRNA pathway mutants relative to wild-type fruit flies, we provide evidence that piRNAs can severely silence the activities of retrotransposons. We incorporate piRNAs into a population genetic framework for retrotransposons and perform forward simulations to model the population dynamics of piRNA loci and their targets. Using parameters optimized for Drosophila melanogaster, our simulation results indicate that (1) piRNAs can significantly reduce the fitness cost of retrotransposons; (2) retrotransposons that generate piRNAs (piRTs) are selectively more advantageous, and such retrotransposon insertions more easily attain high frequency or fixation; (3) retrotransposons that are repressed by piRNAs (targetRTs), however, also have an elevated probability of reaching high frequency or fixation in the population because their deleterious effects are attenuated. By surveying the polymorphisms of piRT and targetRT insertions across nine strains of D. melanogaster, we verified these theoretical predictions with population genomic data. Our theoretical and empirical analysis suggests that piRNAs can significantly increase the fitness of individuals that bear them; however, piRNAs may provide a shelter or Trojan horse for retrotransposons, allowing them to increase in frequency in a population by shielding the host from the deleterious consequences of retrotransposition.